2018
DOI: 10.1016/j.theriogenology.2018.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive stage and sex steroid hormone levels influence the expression of mesenchymal stromal cell (MSC) markers in the equine endometrium

Abstract: Mesenchymal stem or stromal cells (MSCs) play key roles in tissue homeostasis. In the cyclic equine endometrium, this may be regulated by changes in serum concentrations of sex steroid hormones. This study was designed to investigate the changes in endometrial expression of MSC markers during reproductive cycles in mares and the influence of sex steroid hormones on endometrial MSC proliferation in vitro. Endometrial biopsies were collected from pony mares at different reproductive stages (estrus; day 5 and 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…These results are consistent with previous studies reporting the ability of MSCs to restore ovarian structure and sex hormone secretion [ 22 , 27 , 28 ]. Furthermore, previous studies have demonstrated that the number of MSCs in different cell cycle stages can be adjusted by adjusting the concentrations of sex hormones [ 29 , 30 ], suggesting that after BMMSCs restore the secretion of sex hormones, sex hormones may in turn regulate the biological function of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies reporting the ability of MSCs to restore ovarian structure and sex hormone secretion [ 22 , 27 , 28 ]. Furthermore, previous studies have demonstrated that the number of MSCs in different cell cycle stages can be adjusted by adjusting the concentrations of sex hormones [ 29 , 30 ], suggesting that after BMMSCs restore the secretion of sex hormones, sex hormones may in turn regulate the biological function of MSCs.…”
Section: Discussionmentioning
confidence: 99%